THE TEACHERS' CLINIC. - Kaulback, Frank S.; Ingraham, Howell A.; Rushing, Reginald; Littleton, A. C. (The Accounting Review, 1951)
Abstract Many of the experienced teachers, as well as some of the new ones, have developed devices and techniques for the presentation of certain knotty aspects of accounting. This article presents suggestions that might well be made available to other members of the teaching profession through publication in the magazine "Accounting Review." This article presents a method of elementary presentation of volume, cost and profit relationships. The material that follows is designed to be used in the classroom as a simple but highly effective method of explaining and illustrating (a) the concept of unit costs, and practical managerial uses of unit costs (b) the mild enigma that a reduction of unit sales price can result on occasion in an increase of aggregate net profits, and(c) the concepts of marginal costs, break-even point, and optimum profits. A class period of one hour is usually sufficient for presentation and discussion of the subject. The material should be presented in a sequence of steps.